ANALISIS PENGARUH INTELLECTUAL CAPITAL, PROFIT SHARING RATIO, ZAKAT PERFORMANCE RATIO, ISLAMIC INCOME RATIO DAN INCOME DIVERSIFICATION TERHADAP RETURN ON ASSET - Titi Indrayani; Saiful Anwar (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study aims to determine the effect of intellectual capital, profit sharing ratio, zakat performance ratio, islamic income ratio and income diversification on retuen on assets (case study of Islamic Commercial Bank for the 2015-2020 period). This research uses quantitative descriptive research. The sample used in the study were 7 islamic commercial banks. The analysis tool in this study uses multiple liniear regression with Eviews application tools. Based on the test result, it was found that partially intellectual capital variabels had a significant positive effect on ROA, profit sharing ration had a significant negative effect on ROA, zakat performance ratio, islamic income ratio and income diversification have a positive and significant effect on ROA